Copolymer, and electroluminescent device material and electroluminescent device using said copolymer
The problem of insufficient glow efficiency and durability of existing equipment is solved by using materials containing specific copolymer structural units of carbozolene in the backbone in the electroluminescent device, and more efficient and longer-lasting electroluminescent performance is achieved.
Patent Information
- Application Number
- JP2020202696
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-07
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-12-07
AI Technical Summary
The glow efficiency and durability (especially glow life) of existing quantum dot electroluminescent devices are insufficient.
A specific copolymer is employed whose structural units contain a specific structure of carbazolene in the backbone, through which the material properties of the electroluminescent device are improved.
Improves glow efficiency and durability (especially glow life) of electroluminescent devices and achieves higher current efficiency and lower driving voltages.
Smart Images

Figure 0007658740000039 
Figure 0007658740000001 
Figure 0007658740000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a copolymer, and an electroluminescence device material and an electroluminescence device using the copolymer. [Background technology]
[0002] Research and development of electroluminescence elements (EL elements) is being actively carried out. In particular, EL elements are considered to be promising for use as inexpensive solid-state light-emitting large-area full-color display elements and writing light source arrays. EL elements are light-emitting elements having a thin film of several nanometers to several hundred nanometers between an anode and a cathode. EL elements usually further have a hole transport layer, a light-emitting layer, an electron transport layer, and the like.
[0003] Of these, the light-emitting layer can be made of fluorescent or phosphorescent materials. Phosphorescent materials are expected to have about four times the luminous efficiency of fluorescent materials. In addition, to cover a wide color gamut, RGB light sources are required to have a narrow emission spectrum with a half-width. In particular, deep blue is required for blue, but currently no element has been found that satisfies the requirements for long life and color purity.
[0004] As a method for solving these problems, there is a light-emitting device that uses "quantum dots," an inorganic light-emitting material, as a light-emitting material (Patent Document 1). Quantum dots (QDs) are semiconductor materials with a crystal structure of several nanometers in size, and are composed of hundreds to thousands of atoms. Quantum dots have a large surface area per unit volume because they are very small in size. Therefore, most of the atoms are present on the surface of the nanocrystals, and they exhibit quantum confinement effects. Due to this quantum confinement effect, quantum dots can adjust the emission wavelength simply by adjusting their size, and have characteristics such as excellent color purity and high PL (photoluminescence) emission efficiency, so they have attracted much attention. A quantum dot electroluminescence device (QD LED) is known to have a three-layer structure including a quantum dot emission layer in between, a hole transport layer (HTL) and an electron transport layer (ETL) on both sides. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2010-199067 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, an electroluminescence element (particularly a quantum dot electroluminescence element) using the hole transport material described in Patent Document 1 has a problem in that it is not possible to achieve sufficient luminous efficiency and durability (particularly luminous lifetime).
[0007] Therefore, an object of the present invention is to provide a means capable of improving the luminous efficiency and durability (particularly the luminous life span) of an electroluminescent element (particularly a quantum dot electroluminescent element). [Means for solving the problem]
[0008] The present inventors have conducted intensive research to solve the above problems, and as a result, have found that the above problems can be solved by using a polymer compound having a specific structure, thereby completing the present invention.
[0009] That is, the above object can be achieved by a copolymer having a constitutional unit represented by the following formula (1).
[0010] [ka]
[0011] In formula (1), X is a single bond, -L 1 -or-L 1 -L 1 -, where L 1 each independently represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 25 carbon atoms, L 2 represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 3 to 25 ring atoms, Ar 1 and Ar 2 each independently represents a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having from 3 to 25 ring atoms, Y is a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 60 carbon atoms; or a substituted or unsubstituted divalent aromatic heterocyclic group having 3 to 60 ring atoms, At this time, L 2 , Ar 1 and Ar2 satisfies at least one of the following conditions (i) and (ii): (i) Ar 1 and Ar 2 represent different groups; (ii) L 2 and Ar 1 form a ring with each other. Effect of the Invention
[0012] According to the present invention, it is possible to improve the luminous efficiency and durability (particularly the luminous life span) of an electroluminescence element (particularly a quantum dot electroluminescence element). [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic diagram showing an electroluminescence element according to one embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] In a first aspect, the present invention provides a copolymer having a constitutional unit represented by the following formula (1):
[0015] [ka]
[0016] In formula (1), X is a single bond, -L 1 -or-L 1 -L 1 -, where L 1 each independently represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 25 carbon atoms, L 2 represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 3 to 25 ring atoms, Ar 1 and Ar 2each independently represents a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having from 3 to 25 ring atoms, Y is a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 60 carbon atoms; or a substituted or unsubstituted divalent aromatic heterocyclic group having 3 to 60 ring atoms, At this time, L 2 , Ar 1 and Ar 2 satisfies at least one of the following conditions (i) and (ii): (i) Ar 1 and Ar 2 represent different groups; (ii) L 2 and Ar 1 form a ring with each other.
[0017] In this specification, the "structural unit represented by formula (1)" is also referred to as "structural unit (1)" or "structural unit (1) according to the present invention." The following structure in the "structural unit represented by formula (1)":
[0018] [ka]
[0019] The structural unit having the following structure in the "structural unit represented by formula (1)" is also referred to as "structural unit A" or "structural unit A according to the present invention."
[0020] [ka]
[0021] A structural unit having the formula (1) is also referred to as "structural unit B" or "structural unit B according to the present invention." A copolymer having a structural unit represented by formula (1) is also referred to as "copolymer" or "copolymer according to the present invention."
[0022] In a second aspect, there is provided an electroluminescent device material comprising the copolymer according to the present invention.
[0023] In a third aspect, the present invention provides an electroluminescent device comprising a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, wherein at least one layer of the organic films comprises the copolymer according to the present invention. In this specification, the electroluminescent device is also simply referred to as "LED". The quantum dot electroluminescent device is also simply referred to as "QLED". The organic electroluminescent device is also simply referred to as "OLED".
[0024] Various low molecular weight materials and polymeric materials are used as materials for composing the light emitting layer and carrier transport layer of an electroluminescent element. Among these, low molecular weight materials are excellent in terms of efficiency and life of the element. However, when using low molecular weight materials, there is a problem that the manufacturing cost is high because it is necessary to prepare the element by a vacuum process. On the other hand, as a polymeric material, TFB and the like are known as hole transport materials (for example, paragraph "0037" of Patent Document 1). However, it cannot be said that such polymeric materials have sufficiently long luminous efficiency and durability (luminous life) (see Comparative Example 1 below). For this reason, the development of a polymeric material that can improve luminous efficiency and durability (luminous life) was required. The present inventors have conducted extensive research into the above problem. As a result, it has been found that by applying a copolymer having the structural unit A of the above formula (1) to an electroluminescent element, durability (luminous life) can be improved compared to the case where a known material is used. Furthermore, it has been found that by applying a copolymer having the structural unit A of the above formula (1) to an electroluminescent element, high luminous efficiency can be achieved. The mechanism by which the above-mentioned action and effect of the present invention is achieved is presumed to be as follows. In the structural unit A of the above formula (1), carbazole is present in the main chain. This deepens the HOMO level of the copolymer according to the present invention, thereby improving the luminous efficiency. In addition, the structural unit A of the above formula (1) is L 2 , Ar 1お And Ar2 Condition (i): Ar 1 and Ar 2 represent different groups" and "Condition (ii): L 2 and Ar 1 form a ring with each other". That is, the side chain becomes an asymmetric amine. As a result, the molecular orbitals of the copolymer according to the present invention are delocalized not only in the main chain but also in the side chain, so that the hole transfer speed is increased and durability (light emission life) is improved. More specifically, since conventional polymer materials do not have a sufficient hole transfer speed, the hole transfer speed is slower than the electron transfer speed, and the binding of holes and electrons occurs mainly in the region of the hole transport layer side in the light emitting layer. As a result, the region of the hole transport layer side in the light emitting layer is easily deteriorated, and it is considered that sufficient durability (light emission life) was not obtained. Since the hole transfer speed of the copolymer according to the present invention is almost the same as the electron transfer speed, the light emitting region in the light emitting layer is wide. As a result, local deterioration in the light emitting layer can be prevented, and durability (light emission life) can be improved.
[0025] Therefore, an electroluminescence device (particularly a quantum dot electroluminescence device) using a copolymer having the structural unit A of the above formula (1) can exhibit high luminous efficiency and can also improve durability (particularly luminous lifetime).
[0026] In addition, the copolymer according to the present invention has excellent film-forming properties and solvent solubility, so that it can be formed into a film by a wet (coating) method. Therefore, by using the copolymer according to the present invention, it is possible to increase the area of an electroluminescence element and achieve high productivity. The above-mentioned effect can be effectively exhibited when the copolymer according to the present invention is applied to an EL element, particularly a hole transport layer or a hole injection layer of a QLED.
[0027] It should be noted that the above mechanism is merely speculation, and the present invention is not limited to the above mechanism.
[0028] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to the following embodiment. In addition, the drawings are exaggerated for convenience of explanation, and the dimensional ratios of each component in each drawing may differ from the actual ratios. In addition, when the embodiment of the present invention is described with reference to the drawings, the same elements are given the same reference numerals in the description of the drawings, and duplicated explanations are omitted.
[0029] In this specification, unless otherwise specified, operations and measurements of physical properties are performed under conditions of room temperature (20° C. or higher and 25° C. or lower) and relative humidity of 40% RH or higher and 50% RH or lower.
[0030] In this specification, unless otherwise defined, "substituted" refers to being substituted with an alkyl group, a cycloalkyl group, a hydroxyalkyl group, an alkoxyalkyl group, an alkoxy group, a cycloalkoxy group, an alkenyl group, an alkynyl group, an amino group, an aryl group, an aryloxy group, an alkylthio group, a cycloalkylthio group, an arylthio group, an alkoxycarbonyl group, an aryloxycarbonyl group, a hydroxyl group (-OH), a carboxyl group (-COOH), a thiol group (-SH), or a cyano group (-CN). Note that the substituent that may be present is not the same as the group that is substituted. For example, an alkyl group is not substituted with an alkyl group.
[0031] Here, the alkyl group as a substituent may be either linear or branched, and is preferably a linear alkyl group having 1 to 20 carbon atoms and a branched alkyl group having 3 to 20 carbon atoms. Specific examples include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, a 1,4-dimethylpentyl group, a 3-ethylpentyl group, a 2-methyl-1-isopropylpropyl group, a 1-ethyl-3-methyl Examples of such alkyl groups include ethylbutyl group, n-octyl group, 2-ethylhexyl group, 3-methyl-1-isopropylbutyl group, 2-methyl-1-isopropyl group, 1-tert-butyl-2-methylpropyl group, n-nonyl group, 3,5,5-trimethylhexyl group, n-decyl group, isodecyl group, n-undecyl group, 1-methyldecyl group, n-dodecyl group, n-tridecyl group, n-tetradecyl group, n-pentadecyl group, n-hexadecyl group, n-heptadecyl group, n-octadecyl group, n-nonadecyl group, and n-icosyl group.
[0032] Examples of the cycloalkyl group as a substituent include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, and a cyclohexyl group.
[0033] Examples of hydroxyalkyl groups include the above-mentioned alkyl groups substituted with 1 to 3 (preferably 1 to 2, particularly preferably 1) hydroxyl groups (eg, hydroxymethyl group, hydroxyethyl group).
[0034] Examples of the alkoxyalkyl group as a substituent include the above alkyl groups substituted with 1 to 3 (preferably 1 to 2, particularly preferably 1) alkoxy groups as described below.
[0035] The alkoxy group as a substituent may be either linear or branched, and preferably includes linear alkoxy groups having from 1 to 20 carbon atoms and branched alkoxy groups having from 3 to 20 carbon atoms. Examples include methoxy, ethoxy, propoxy, isopropoxy, butoxy, pentyloxy, hexyloxy, heptyloxy, 3-ethylpentyloxy, octyloxy, 2-ethylhexyloxy, nonyloxy, decyloxy, undecyloxy, dodecyloxy, tridecyloxy, tetradecyloxy, pentadecyloxy, hexadecyloxy, heptadecyloxy, and octadecyloxy groups.
[0036] Examples of the cycloalkoxy group as a substituent include a cyclopropyloxy group, a cyclobutyloxy group, a cyclopentyloxy group, and a cyclohexyloxy group.
[0037] Examples of alkenyl groups include vinyl groups, allyl groups, 1-propenyl groups, isopropenyl groups, 1-butenyl groups, 2-butenyl groups, 3-butenyl groups, 1-pentenyl groups, 2-pentenyl groups, 3-pentenyl groups, 1-hexenyl groups, 2-hexenyl groups, 3-hexenyl groups, 1-heptenyl groups, 2-heptenyl groups, 5-heptenyl groups, 1-octenyl groups, 3-octenyl groups, and 5-octenyl groups.
[0038] Examples of the alkynyl group as a substituent include an acetylenyl group, a 1-propynyl group, a 2-propynyl group, a 1-butynyl group, a 2-butynyl group, a 3-butynyl group, a 1-pentetyl group, a 2-pentetyl group, a 3-pentetyl group, a 1-hexynyl group, a 2-hexynyl group, a 3-hexynyl group, a 1-heptynyl group, a 2-heptynyl group, a 5-heptynyl group, a 1-octynyl group, a 3-octynyl group, and a 5-octynyl group.
[0039] The aryl group as the substituent includes an aryl group having a carbon number of 6 to 30. Examples thereof include a phenyl group, a naphthyl group, a biphenyl group, a fluorenyl group, anthryl group, a pyrenyl group, an azulenyl group, an acenaphthylenyl group, a terphenyl group, and a phenanthryl group.
[0040] Examples of the aryloxy group as a substituent include a phenoxy group and a naphthyloxy group.
[0041] Examples of the alkylthio group as a substituent include a methylthio group, an ethylthio group, a propylthio group, a pentylthio group, a hexylthio group, an octylthio group, and a dodecylthio group.
[0042] Examples of the cycloalkylthio group as a substituent include a cyclopentylthio group and a cyclohexylthio group.
[0043] Examples of the arylthio group as a substituent include a phenylthio group and a naphthylthio group.
[0044] Examples of the alkoxycarbonyl group as a substituent include a methyloxycarbonyl group, an ethyloxycarbonyl group, a butyloxycarbonyl group, an octyloxycarbonyl group, and a dodecyloxycarbonyl group.
[0045] Examples of the aryloxycarbonyl group as a substituent include a phenyloxycarbonyl group and a naphthyloxycarbonyl group.
[0046] [Copolymer] The copolymer according to the present embodiment has a structural unit (structural unit (1)) represented by the following formula (1). The copolymer having the following structure has a structural unit A. Therefore, an electroluminescence device (particularly a quantum dot electroluminescence device) having the copolymer according to the present embodiment (particularly in the hole transport layer) has excellent luminous efficiency and durability (long luminous life). In addition, high current efficiency and low driving voltage can be achieved. The copolymer according to the present embodiment may contain one structural unit (structural unit (1)) of formula (1), or may contain two or more structural units (1). Note that the multiple structural units (1) may be present in a block form or random form. In addition, when two or more structural units (1) are present, the "structural unit A" in each structural unit (1) may be the same or different. Similarly, when two or more structural units (1) are present, the "structural unit B" in each structural unit (1) may be the same or different.
[0047] [ka]
[0048] In the above formula (1), L 2 , Ar 1 and Ar 2 Condition (i): Ar 1 and Ar 2 represent different groups" and "Condition (ii): L 2 and Ar 1 and (ii) are each independently a ring.
[0049] X is a single bond, -L 1 -or-L 1 -L 1 In this case, L 1 Each of L independently represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 25 carbon atoms. 1When a plurality of are present, they may be the same or different. The divalent aromatic hydrocarbon group having 6 to 25 carbon atoms is not particularly limited, but specific examples include divalent groups derived from aromatic hydrocarbon compounds such as benzene (phenylene group), pentalene, indene, naphthalene, anthracene, azulene, heptalene, acenaphthene, phenalene, fluorene, phenanthroline, biphenyl, terphenyl, quaterphenyl, quinquiphenyl, pyrene, 9,9-diphenylfluorene, 9,9'-spirobi[fluorene], and 9,9-dialkylfluorene. The divalent aromatic hydrocarbon group having 6 to 25 carbon atoms may also be a divalent group derived from a structure in which two or more of the above-mentioned aromatic hydrocarbon compounds are combined. Of these, X is a single bond, and a divalent group (L) derived from a compound selected from benzene, fluorene, dibenzofuran, dibenzothiophene, and biphenyl. 1 More preferably, X is a single bond or a divalent group (L) derived from a compound selected from benzene (o-, m-, or p-phenylene), dibenzofuran, and fluorene. 1 ). More preferably, X is a single bond or a phenylene group (particularly a p-phenylene group). Particularly preferably, X is a single bond. Such an X allows the HOMO level of the copolymer to be more appropriately controlled. In addition, it is possible to achieve higher hole injection properties, higher triplet energy levels, lower driving voltages, and film-formability, as well as a balance between any two or more of these (particularly a balance between hole injection properties and film-formability).
[0050] In the above preferred embodiment, L 1 may be unsubstituted or any hydrogen atom may be substituted with a substituent. 1 When any hydrogen atom of L is substituted, the number of substituents to be introduced is not particularly limited, but is preferably 1 or more and 3 or less, more preferably 1 or more and 2 or less, and particularly preferably 1. 1 When L has a substituent, the bonding position of the substituent is not particularly limited. 1 L 2It is preferable that the substituent is located as far away as possible from the nitrogen atom of the side chain to which it is linked via the substituent. The presence of the substituent at such a position allows the HOMO level of the copolymer to be more appropriately controlled. In addition, it is possible to achieve higher hole injection properties, higher triplet energy levels, lower driving voltages, and film-forming properties, as well as a balance between any two or more of these (particularly a balance between hole injection properties and film-forming properties).
[0051] L 2 represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 3 to 25 ring atoms. 2 When a plurality of groups are present, they may be the same or different. As the aromatic hydrocarbon group having 6 to 25 carbon atoms, the above L 1 The aromatic hydrocarbon group in the above formula (I) is exemplified in the same manner. The aromatic heterocyclic group having 3 to 25 ring atoms is not particularly limited, but specific examples thereof include acridine, phenazine, benzoquinoline, benzoisoquinoline, phenanthridine, phenanthroline, anthraquinone, fluorenone, dibenzofuran, phenyldibenzofuran, dibenzothiophene, phenyldibenzothiophene, carbazole, imidazophenanthridine, benzimidazophenanthridine, azadibenzofuran, 9-phenylcarbazole, azacarbazole, azadibenzothiophene, diazadibenzofuran, diazacarbazole, diazadibenzothiophene, xanthone, thioxanthone, pyridine, quinoline, anthraquinoline, and other heterocyclic aromatic compound-derived groups. The aromatic hydrocarbon group having 6 to 25 carbon atoms and the aromatic heterocyclic group having 3 to 25 ring atoms can be exemplified in the above formula (I). 1 or may be a group derived from a structure in which two or more of the aromatic hydrocarbon compounds in 1and one or more of the above-mentioned heterocyclic aromatic compounds. Among these, the aromatic hydrocarbon compound-derived group or the aromatic heterocyclic group having 3 to 25 ring atoms is preferably a group derived from a compound selected from benzene (phenylene group), biphenyl, quaterphenyl, fluorene, dibenzofuran, and dibenzothiophene, more preferably a group derived from a compound selected from benzene (phenylene group), biphenyl, fluorene, and dibenzofuran, and even more preferably a group derived from a compound selected from benzene (phenylene group) and biphenyl. According to a particularly preferred embodiment, L 2 represents a group selected from the following group:
[0052] [ka]
[0053] Here, * represents a bond to the nitrogen atom of the carbazole ring in the main chain (a bond without * represents a bond to the nitrogen atom of the arylamine in the side chain).
[0054] Among these groups, (3-1), (3-4), and (3-13) to (3-24) are particularly preferred, and (3-4) is the most preferred. 2 If L is 0.01, the HOMO level of the copolymer can be more appropriately controlled. In addition, it is possible to achieve higher hole injection properties, higher triplet energy levels, lower driving voltages, and film-forming properties, as well as a balance between any two or more of these (particularly the balance between hole injection properties and film-forming properties). 2 , Ar 1 and Ar 2 However, "Condition (ii): L 2 and Ar 1 form a ring with each other, L 2 is a trivalent group, and if condition (ii) is not satisfied, L 2 is a divalent group.
[0055] Ar 1and Ar 2 each independently represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 3 to 25 ring atoms. 1 and Ar 2 When a plurality of L are present, they may be the same or different. As the aromatic hydrocarbon group having 6 to 25 carbon atoms and the aromatic heterocyclic group having 3 to 25 ring atoms, the above L 1 The group derived from an aromatic hydrocarbon compound in the above L 2 The group derived from a heterocyclic aromatic compound in the above L 1 A group derived from a structure obtained by combining two or more aromatic hydrocarbon compounds in the above L 2 A group derived from a structure obtained by combining two or more of the heterocyclic aromatic compounds in 1 and one or more of the above L 2 The same examples are groups derived from the structure in which the heterocyclic aromatic compound in the above formula is combined. Among these, the aromatic hydrocarbon group having 6 to 25 carbon atoms or the aromatic heterocyclic group having 3 to 25 ring atoms is preferably a group derived from a compound selected from benzene, biphenyl, fluorene, 9,9-diphenylfluorene, 9,9'-spirobi[fluorene], 9,9-dialkylfluorene, dibenzofuran, phenyldibenzofuran, dibenzothiophene, and phenyldibenzothiophene, more preferably a group derived from a compound selected from benzene, biphenyl, fluorene, 9,9-diphenylfluorene, 9,9'-spirobi[fluorene], 9,9-dialkylfluorene, dibenzofuran, and phenyldibenzofuran, and even more preferably a group derived from a compound selected from benzene, biphenyl, 9,9-diphenylfluorene, 9,9-dialkylfluorene, and dibenzofuran. Such Ar 1 and Ar 2If Ar is used, the hole transfer rate of the copolymer can be increased, thereby improving durability (light emission life). In addition, higher hole injection properties, higher triplet energy levels, lower driving voltages, and film formability can be achieved, as well as a balance between any two or more of these properties (particularly a balance between hole injection properties and film formability). 2 is a monovalent group. On the other hand, L 2 , Ar 1 and Ar 2 However, "Condition (ii): L 2 and Ar 1 form a ring with each other, Ar 1 is a divalent group, and if condition (ii) is not satisfied, then Ar 1 is a monovalent group.
[0056] According to a preferred embodiment, L 2 , Ar 1 and Ar 2 Condition (i): Ar 1 and Ar 2 represent different groups" and Ar 1 and Ar 2 each independently represents a group selected from the following group:
[0057] [ka]
[0058] Here, each R independently represents a hydrogen atom or a linear or branched hydrocarbon group having 1 to 14 carbon atoms.
[0059] Examples of the linear or branched saturated hydrocarbon group having 1 to 14 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, a 1,4-dimethylpentyl group, a 3-ethylpentyl group, a 2-methyl-1-isopropylpropyl group, a 1-ethyl-3-methylbutyl group, an n-octyl group, a 2-ethylhexyl group, a 3-methyl-1-isopropylbutyl group, a 2-methyl-1-isopropyl group, a 1-tert-butyl-2-methylpropyl group, an n-nonyl group, a 3,5,5-trimethylhexyl group, and an n-decyl group. isodecyl group, n-undecyl group, 1-methyldecyl group, n-dodecyl group, n-tridecyl group, n-tetradecyl group, vinyl group, allyl group, 1-propenyl group, isopropenyl group, 1-butenyl group, 2-butenyl group, 3-butenyl group, 1-pentenyl group, 2-pentenyl group, 3-pentenyl group, 1-hexenyl group, 2-hexenyl group, 3-hexenyl group, 1-heptenyl group, 2-heptenyl group, 5-heptenyl group, 1-octenyl group, Examples of the aryl group include octenyl, 3-octenyl, 5-octenyl, acetylenyl, 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentetyl, 2-pentetyl, 3-pentetyl, 1-hexynyl, 2-hexynyl, 3-hexynyl, 1-heptynyl, 2-heptynyl, 5-heptynyl, 1-octynyl, 3-octynyl, and 5-octynyl.
[0060] Of these groups, Ar 1 and Ar 2 Particularly preferred are (2-1) to (2-24), and most preferred are (2-1) to (2-4), (2-16), (2-23), and (2-27). 1 and Ar 2As the combination of Ar, the combination of (2-2) and (2-23), the combination of (2-3) and (2-23), the combination of (2-4) and (2-23), the combination of (2-16) and (2-27), and the combination of (2-23) and (2-27) are preferred. In this case, each R is preferably a linear or branched saturated hydrocarbon group having 1 to 14 carbon atoms, more preferably a linear or branched saturated hydrocarbon group having 1 to 8 carbon atoms, and further preferably a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, or a 1,2-dimethylbutyl group. Such Ar 1 and Ar 2 If the above formula is used, the hole transfer rate of the copolymer can be increased, thereby improving durability (luminescence life span). In addition, higher hole injection properties, higher triplet energy level, lower driving voltage, film formability, and a balance between any two or more of these properties (particularly the balance between hole injection properties and film formability) can be achieved.
[0061] According to another preferred embodiment, L 2 , Ar 1 and Ar 2 Condition (ii): L 2 and Ar 1 form a ring with each other" and -L 2 -N(Ar 1 )(Ar 2 ) represents a group selected from the following group:
[0062] [ka]
[0063] However, Ar 2 is defined in the same way as in equation (1).
[0064] Among these groups, (4-1), (4-4) and (4-7) are particularly preferred, and (4-4) is the most preferred. 2 -N(Ar 1 )(Ar 2 ), the hole transfer rate of the copolymer can be increased, thereby improving durability (luminescence life). In addition, higher hole injection properties, higher triplet energy level, lower driving voltage, film formability, and a balance between any two or more of these (particularly the balance between hole injection properties and film formability) can be achieved.
[0065] Y represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having 3 to 60 ring atoms. The divalent aromatic hydrocarbon group having 6 to 60 carbon atoms and the divalent aromatic heterocyclic group having 3 to 60 ring atoms are exemplified by the above L. 1 The divalent group derived from an aromatic hydrocarbon compound in the above L 2 A divalent group derived from a heterocyclic aromatic compound in the above L 1 A divalent group derived from a structure in which two or more aromatic hydrocarbon compounds in the above formula are combined, 2 A divalent group derived from a structure in which two or more heterocyclic aromatic compounds in 1 and one or more of the above L 2The divalent group derived from the structure obtained by combining the heterocyclic aromatic compound in the above is exemplified in the same manner. Among these, a divalent aromatic hydrocarbon group having 6 to 25 carbon atoms or a divalent aromatic heterocyclic group having 3 to 25 ring atoms is preferred, and a compound selected from benzene (phenylene group), biphenyl, quaterphenyl, fluorene, dibenzofuran, and dibenzothiophene or a divalent group derived from a structure obtained by combining these compounds is more preferred, and a compound selected from benzene (phenylene group), fluorene, and dibenzofuran or a divalent group derived from a structure obtained by combining these compounds is even more preferred. With such Y, the HOMO level of the copolymer can be more appropriately controlled. In addition, a higher hole injection property, a higher triplet energy level, and a lower driving voltage and film-forming property can be achieved, as well as a balance between any two or more of these (particularly a balance between hole injection property and film-forming property).
[0066] According to one preferred embodiment, Y represents a group selected from the following group:
[0067] [ka]
[0068] However, R 1 , R 2 and R 4 each independently represents a hydrogen atom, a linear or branched saturated hydrocarbon group having from 1 to 14 carbon atoms, or an aromatic hydrocarbon group having from 6 to 28 carbon atoms; R 3 each independently represents a linear or branched saturated hydrocarbon group having 1 to 14 carbon atoms.
[0069] Examples of the linear or branched saturated hydrocarbon group having 1 to 14 carbon atoms include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, an n-pentyl group, an isopentyl group, a tert-pentyl group, a neopentyl group, a 1,2-dimethylpropyl group, an n-hexyl group, an isohexyl group, a 1,3-dimethylbutyl group, a 1-isopropylpropyl group, a 1,2-dimethylbutyl group, an n-heptyl group, a 1,4-dimethylpentyl group, a 2-dimethylpentyl group, a 1-dimethylpentyl group, a 2 ... Examples of such groups include an n-butyl group, a 3-ethylpentyl group, a 2-methyl-1-isopropylpropyl group, a 1-ethyl-3-methylbutyl group, an n-octyl group, a 2-ethylhexyl group, a 3-methyl-1-isopropylbutyl group, a 2-methyl-1-isopropyl group, a 1-tert-butyl-2-methylpropyl group, an n-nonyl group, a 3,5,5-trimethylhexyl group, an n-decyl group, an isodecyl group, an n-undecyl group, a 1-methyldecyl group, an n-dodecyl group, an n-tridecyl group, and an n-tetradecyl group.
[0070] Examples of the aromatic hydrocarbon group having 6 to 28 carbon atoms include a phenyl group, a naphthyl group, a biphenyl group, a fluorenyl group, anthryl group, a pyrenyl group, an azulenyl group, an acenaphthylenyl group, a terphenyl group, and a phenanthryl group.
[0071] Among these groups, (5-1) to (5-7) are more preferred, and (5-2) and (5-5) are particularly preferred. In this case, R 1 , R 2 , R 3 and R 4are each independently preferably a linear or branched saturated hydrocarbon group having 1 to 14 carbon atoms, more preferably a linear or branched saturated hydrocarbon group having 6 to 14 carbon atoms, and further preferably an n-octyl group, a 2-ethylhexyl group, or an n-dodecyl group. Such a Y allows the HOMO level of the copolymer to be more appropriately controlled. In addition, higher hole injection properties, higher triplet energy level, lower driving voltage, and film-forming properties can be achieved, as well as a balance between any two or more of these (particularly a balance between hole injection properties and film-forming properties).
[0072] As described above, the copolymer according to this embodiment may be composed of only the structural unit (1). Alternatively, the copolymer according to this embodiment may further contain other structural units other than the structural unit (1). When other structural units are contained, the other structural units are not particularly limited as long as they do not impair the effects of the copolymer (particularly high triplet energy level, low driving voltage). Specific examples include structural units selected from the following group. In the following, the structural units shown in the following group are also referred to as "structural unit (2)".
[0073] [ka]
[0074] The composition of the structural unit (2) in the copolymer of this embodiment is not particularly limited. Considering the ease of film formation by the obtained polymer compound and the effect of further improving the coating strength, the structural unit (2) is preferably 1 mol% or more and 10 mol% or less with respect to the total structural units constituting the copolymer. Note that, when the copolymer contains two or more kinds of structural units (2), the content of the structural unit (2) means the total amount of the structural units (2).
[0075] The weight average molecular weight (Mw) of the copolymer is not particularly limited as long as the objective effect of the present invention is obtained. The weight average molecular weight (Mw) is, for example, preferably 8,000 or more and 400,000 or less, more preferably more than 15,000 and less than 350,000. If the weight average molecular weight is such, it is possible to form a layer with a uniform thickness by appropriately adjusting the viscosity of the coating solution for forming a layer (e.g., a hole injection layer, a hole transport layer) using the copolymer.
[0076] The number average molecular weight (Mn) of the copolymer is not particularly limited as long as the objective effect of the present invention is obtained. The number average molecular weight (Mn) is, for example, preferably 5,000 or more and 190,000 or less, more preferably 9,000. With such a number average molecular weight, it is possible to form a layer with a uniform thickness by appropriately adjusting the viscosity of a coating solution for forming a layer (e.g., a hole injection layer, a hole transport layer) using the copolymer. The polydispersity (weight average molecular weight / number average molecular weight) of the copolymer of this embodiment is, for example, 1.4 or more and 4.0 or less, preferably more than 1.5 and less than 3.6.
[0077] Here, the number average molecular weight (Mn) and weight average molecular weight (Mw) are not particularly limited in measurement, and may be measured by a known method or by appropriately modifying a known method. In this specification, the number average molecular weight (Mn) and weight average molecular weight (Mw) are values measured by the following method. The polydispersity (Mw / Mn) of a polymer is calculated by dividing the weight average molecular weight (Mw) by the number average molecular weight (Mn) measured by the following method.
[0078] (Measurement of number average molecular weight (Mn) and weight average molecular weight (Mw)) The number average molecular weight (Mn) and weight average molecular weight (Mw) of the copolymer are measured by SEC (Size Exclusion Chromatography) using polystyrene as a standard substance under the following conditions.
[0079] (SEC measurement conditions) Analytical equipment (SEC): Shimadzu Corporation, Prominence Column: Polymer Laboratories, PLgel MIXED-B Column temperature: 40℃ Flow rate: 1.0mL / min Amount of sample solution injected: 20 μL (polymer concentration: approximately 0.05% by mass) Eluent: tetrahydrofuran (THF) Detector (UV-VIS detector): Shimadzu Corporation, SPD-10AV Standard sample: polystyrene.
[0080] The terminal of the main chain of the copolymer according to this embodiment is not particularly limited and is appropriately determined depending on the type of raw material used, but is usually a hydrogen atom.
[0081] The copolymer according to this embodiment can be synthesized by using a known organic synthesis method. A person skilled in the art can easily understand the specific synthesis method of the copolymer according to this embodiment by referring to the examples described below. Specifically, the copolymer according to this embodiment can be produced by a polymerization reaction using one or more monomers (1) represented by the following formula (1'), or by a copolymerization reaction using one or more monomers (1) represented by the following formula (1') and other monomers corresponding to the other structural units.
[0082] [ka]
[0083] Alternatively, the polymerizable composition can be produced by a copolymerization reaction using one or more monomers (1-1) represented by the following formula (1-1') and one or more monomers (1-2) represented by the following formula (1-2'), or using one or more monomers (1-1) represented by the following formula (1-1'), one or more monomers (1-2) represented by the following formula (1-2'), and other monomers corresponding to the other structural units described above.
[0084] [ka]
[0085] [ka]
[0086] In the present invention, the above-mentioned monomers used in the polymerization of the copolymer can be synthesized by an appropriate combination of known synthesis reactions, and the structure thereof can be confirmed by known methods (for example, NMR, LC-MS, etc.).
[0087] In the above formula (1'), formula (1-1') and formula (1-2'), L 1 , Ar 1 , Ar 2 , Y is defined as in formula (1) above. 1 , Z 2 , Z 1 ', Z 2 ', Z 1 " and Z 2 " are each independently a halogen atom (fluorine atom, chlorine atom, bromine atom, iodine atom, particularly bromine atom) or a group of the following structure. In the following structure, R A ~R D are each independently an alkyl group having 1 to 3 carbon atoms. A ~R D is a methyl group. 1 and Z 2 may be the same or different. Similarly, Z 1 ' and Z 2 Z ′ may be the same or different. 1 " and Z 2 " may be the same or different. Preferably, in the above formula (1'), Z 1 and Z 2 In the above formula (1-1'), Z 1 ' and Z 2In the above formula (1-2'), Z 1 " and Z 2 " are the same; Z in the above formula (1-1') 1 ' and Z 2 ' is Z in the above formula (1-2') 1 " and Z 2 " is preferably different from ".
[0088] [ka]
[0089] [Electroluminescence device materials] The copolymer according to this embodiment is preferably used as an electroluminescence device material. According to this embodiment, an electroluminescence device material having excellent luminous efficiency and durability (especially luminescence life) is provided. In addition, according to the copolymer according to this embodiment, an electroluminescence device material having a high triplet energy level (current efficiency) and a low driving voltage is also provided. Furthermore, the copolymer according to this embodiment exhibits high solubility in a solvent and high heat resistance. Therefore, it can be easily formed into a film (thin film) by a wet (coating) method. Therefore, in a second aspect of the present invention, an electroluminescence device material containing the copolymer according to this embodiment is provided. Or, the use of the copolymer according to the present invention as an electroluminescence device material is provided.
[0090] [Electroluminescent element] As described above, the copolymer according to the present embodiment is preferably used in an electroluminescence element. That is, an electroluminescence element is provided that includes a pair of electrodes and one or more organic films disposed between the electrodes and containing the copolymer according to the present embodiment or an electroluminescence element material. Such an electroluminescence element can exhibit excellent durability (light-emitting life). In addition, such an electroluminescence element can exhibit high light-emitting efficiency (particularly excellent light-emitting efficiency at a low driving voltage). Therefore, in a third aspect, the present invention provides an electroluminescence element that includes a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, at least one layer of the organic film containing the copolymer according to the present embodiment. The object (or effect) of the present invention can also be achieved by such an electroluminescence element according to the present embodiment. As a preferred embodiment of the above aspect, the electroluminescence element further includes a light-emitting layer disposed between the electrodes and containing a light-emitting material capable of emitting light from triplet excitons. The electroluminescent element of this embodiment is an example of the electroluminescent element according to the present invention.
[0091] Furthermore, the present embodiment provides a method for producing an electroluminescence element including a pair of electrodes and one or more organic films disposed between the electrodes and containing the copolymer of the present embodiment, in which at least one of the organic films is formed by a coating method. The present embodiment also provides an electroluminescence element in which at least one of the organic films is formed by a coating method using this method.
[0092] The copolymer of this embodiment and the electroluminescence device material (EL device material) of this embodiment (hereinafter collectively referred to as "copolymer / EL device material") have excellent solubility in organic solvents. Therefore, the copolymer / EL device material of this embodiment is particularly suitable for use in the manufacture of devices (particularly thin films) by a coating method (wet process). For this reason, this embodiment provides a liquid composition containing the copolymer and a solvent or dispersion medium. Such a liquid composition is one example of the liquid composition according to the present invention.
[0093] In addition, the electroluminescent device material according to the embodiment as described above is preferably used for manufacturing a device (particularly a thin film) by a coating method (wet process). From the above viewpoint, the present embodiment provides a thin film containing the copolymer. Such a thin film is an example of the thin film according to the present invention.
[0094] In addition, the copolymer / EL device material according to this embodiment has excellent hole injection properties and hole mobility. Therefore, it can be suitably used in the formation of any organic film such as a hole injection material, a hole transport material, or a light emitting material (host). Among these, from the viewpoint of hole transport properties, it is suitably used as a hole injection material or a hole transport material, and is particularly suitably used as a hole transport material.
[0095] The electroluminescent element according to the present embodiment will be described in detail below with reference to Fig. 1. Fig. 1 is a schematic diagram showing the electroluminescent element according to the present embodiment. In this specification, the "electroluminescent element" may be abbreviated to "EL element".
[0096] As shown in FIG. 1, the EL element 100 according to this embodiment includes a substrate 110, a first electrode 120 disposed on the substrate 110, a hole injection layer 130 disposed on the first electrode 120, a hole transport layer 140 disposed on the hole injection layer 130, an emitting layer 150 disposed on the hole transport layer 140, an electron transport layer 160 disposed on the emitting layer 150, an electron injection layer 170 disposed on the electron transport layer 160, and a second electrode 180 disposed on the electron injection layer 170.
[0097] Here, the copolymer / EL element material of this embodiment is, for example, contained in any of the organic films (organic layers) arranged between the first electrode 120 and the second electrode 180. Specifically, the copolymer / EL element material is preferably contained in the hole injection layer 130 as a hole injection material, the hole transport layer 140 as a hole transport material, or the light emitting layer 150 as a light emitting material (host). It is more preferable that the copolymer / EL element material is contained in the hole injection layer 130 as a hole injection material or in the hole transport layer 140 as a hole transport material. It is particularly preferable that the copolymer / EL element material is contained in the hole transport layer 140 as a hole transport material. That is, in a preferred embodiment of the present invention, the organic film containing the copolymer / EL element material is a hole transport layer, a hole injection layer, or a light emitting layer. In a more preferred embodiment of the present invention, the organic film containing the copolymer is a hole transport layer or a hole injection layer. In a particularly preferred embodiment of the present invention, the organic film containing the copolymer is a hole transport layer.
[0098] The organic film containing the copolymer / EL element material of this embodiment is formed by a coating method (solution coating method). Specifically, the organic film is formed by a solution coating method such as a spin coat method, a casting method, a micro gravure coat method, a gravure coat method, a bar coat method, a roll coat method, a wire bar coat method, a dip coat method, a spray coat method, a screen printing method, a flexographic printing method, an offset printing method, or an ink jet printing method.
[0099] In addition, the solvent used in the solution coating method can be any solvent that can dissolve the copolymer / EL element material, and can be appropriately selected depending on the type of copolymer used. For example, toluene, xylene, ethylbenzene, diethylbenzene, methylene, propylbenzene, cyclohexylbenzene, dimethoxybenzene, anisole, ethoxytoluene, phenoxytoluene, isopropylbiphenyl, dimethylanisole, phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, cyclohexane, etc. are exemplified. In addition, the amount of the solvent used is not particularly limited, but considering the ease of coating, etc., it is an amount such that the concentration of the copolymer is preferably about 0.1% by mass or more and 10% by mass or less, more preferably about 0.5% by mass or more and 5% by mass or less.
[0100] The method for forming the layer other than the organic film containing the copolymer / EL element material is not particularly limited. The layer other than the organic film containing the copolymer / EL element material of the present embodiment may be formed by, for example, a vacuum deposition method or a solution coating method.
[0101] A substrate used in a general EL device can be used as the substrate 110. For example, the substrate 110 may be a glass substrate, a semiconductor substrate such as a silicon substrate, or a transparent plastic substrate.
[0102] A first electrode 120 is formed on the substrate 110. Specifically, the first electrode 120 is an anode, and is made of a metal, an alloy, a conductive compound, or the like that has a large work function. For example, the first electrode 120 is made of indium tin oxide (InO 2 ), which has excellent transparency and conductivity. 2 O 3 -SnO 2 :ITO), indium zinc oxide (In 2 O 3 -ZnO), Tin Oxide (SnO 2 The first electrode 120 may be formed as a transmissive electrode using zinc oxide (ZnO) or the like. The first electrode 120 may be formed as a reflective electrode by laminating magnesium (Mg), aluminum (Al) or the like on the transparent conductive film. After the first electrode 120 is formed on the substrate 110, cleaning and UV-ozone treatment may be performed, if necessary.
[0103] A hole injection layer 130 is formed on the first electrode 120. The hole injection layer 130 is a layer that facilitates the injection of holes from the first electrode 120, and may be formed to a thickness of about 10 nm to about 1000 nm, more specifically, about 20 nm to about 50 nm (dry film thickness; the same applies below).
[0104] The hole injection layer 130 can be formed of a known hole injection material. Examples of known hole injection materials for forming the hole injection layer 130 include poly(ether ketone)-containg triphenylamine (TPAPEK), 4-isopropyl-4'-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (PPBI), N,N'-diphenyl-N,N'-bis-[4-(phenyl-m-tolyl-amino)-phenyl]-biphenyl-4,4'-diamine (DNTPD), copper phthalocyanine (CuPc), and the like. phthalocyanine), 4,4',4”-tris(3-methylphenylphenylamino)triphenylamine (m-MTDATA), N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB), 4,4',4”-tris(diphenylamino)triphenylamine (TDATA), 4,4',4”-tris(N,N-2-naphthylphenylamino)triphenylamine (2-TNATA), polyaniline / dodecylbenzenesulphonic acid acid), poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (poly(3,Examples of such a polymer include 4-ethylenedioxythiophene / poly(4-styrenesulfonate):PEDOT / PSS, and polyaniline / 10-camphorsulfonic acid.
[0105] The hole transport layer 140 is formed on the hole injection layer 130. The hole transport layer 140 is a layer having a function of transporting holes, and may be formed to a thickness of, for example, about 10 nm to about 150 nm, more specifically, about 20 nm to about 50 nm. The hole transport layer 140 is preferably formed by a solution coating method using the copolymer of this embodiment. This method can extend the durability (light emission life) of the EL element 100. It is also possible to improve the performance (light emission efficiency) of the EL element 100. It is also possible to improve the current efficiency of the EL element 100 and reduce the driving voltage. In addition, since the hole transport layer can be formed by the solution coating method, it can be efficiently formed in a large area.
[0106] However, when any other organic film of the EL element 100 contains the copolymer according to this embodiment, the hole transport layer 140 may be formed of a known hole transport material. Examples of known hole transport materials include 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), carbazole derivatives such as N-phenylcarbazole and polyvinylcarbazole, N,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1-biphenyl]-4,4'-diamine (N ,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1-biphenyl]-4,4'-diamine (TPD), 4,4',4"-tris(N-carbazolyl)triphenylamine (TCTA), and N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (NPB).
[0107] The light-emitting layer 150 is formed on the hole transport layer 140. The light-emitting layer 150 is a layer that emits light by fluorescence, phosphorescence, or the like, and is formed by using a vacuum deposition method, a spin coating method, an inkjet printing method, or the like. The light-emitting layer 150 may be formed to a thickness of, for example, about 10 nm or more and about 60 nm or less, more specifically, about 20 nm or more and about 50 nm or less. As the light-emitting material of the light-emitting layer 150, a known light-emitting material can be used. However, the light-emitting material contained in the light-emitting layer 150 is preferably a light-emitting material that can emit light from triplet excitons (i.e., phosphorescence emission). In such a case, the driving life of the EL element 100 can be further improved.
[0108] The light-emitting layer 150 is not particularly limited and may have a known configuration. Preferably, the light-emitting layer contains semiconductor nanoparticles or an organometallic complex. That is, in a preferred embodiment of the present invention, the organic film has a light-emitting layer containing semiconductor nanoparticles or an organometallic complex. When the light-emitting layer contains semiconductor nanoparticles, the EL element is a quantum dot electroluminescent element (QLED), a quantum dot light-emitting element, or a quantum dot light-emitting element. When the light-emitting layer contains an organometallic complex, the EL element is an organic electroluminescent element (OLED).
[0109] In the case of a configuration (QLED) in which the light-emitting layer contains semiconductor nanoparticles, the light-emitting layer is a single layer or multiple layers of a large number of semiconductor nanoparticles (quantum dots). Here, the semiconductor nanoparticles (quantum dots) are particles of a certain size that have a quantum confinement effect. The diameter of the semiconductor nanoparticles (quantum dots) is not particularly limited, but is about 1 nm or more and 10 nm or less.
[0110] The semiconductor nanoparticles (quantum dots) arranged in the light-emitting layer can be synthesized by a wet chemical process, a metal organic chemical vapor deposition process, a molecular beam epitaxy process, or other similar processes, etc. Among them, the wet chemical process is a method in which a precursor material is put into an organic solvent to grow particles.
[0111] In the wet chemical process, the organic solvent naturally coordinates with the surface of the quantum dot crystals as the crystals grow, and acts as a dispersant to regulate the growth of the crystals. Therefore, the wet chemical process can control the growth of semiconductor nanoparticles more easily and at lower cost than gas phase deposition methods such as Metal Organic Chemical Vapor Deposition (MOCVD) and Molecular Beam Epitaxy (MBE).
[0112] By adjusting the size of semiconductor nanoparticles (quantum dots), the energy band gap can be adjusted, and light of various wavelengths can be obtained in the light-emitting layer (quantum dot light-emitting layer). Therefore, by using multiple quantum dots of different sizes, it is possible to realize a display that emits (or emits) light of multiple wavelengths. The size of the quantum dots can be selected to emit red, green, and blue light so that a color display can be constructed. The sizes of the quantum dots can also be combined to emit various color lights to emit white light.
[0113] As the semiconductor nanoparticles (quantum dots), a semiconductor material selected from the group consisting of II-VI group semiconductor compounds; III-V group semiconductor compounds; IV-VI group semiconductor compounds; IV group elements or compounds; and combinations thereof can be used.
[0114] The II-VI semiconductor compound is not particularly limited, but may be selected from the group consisting of two-element compounds selected from the group consisting of CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, and mixtures thereof; three-element compounds selected from the group consisting of CdSeS, CdSeTe, CdSTe, ZnSeS, ZnTeSe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, and mixtures thereof; and four-element compounds selected from the group consisting of CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, and mixtures thereof.
[0115] The III-V semiconductor compound is not particularly limited, but may be selected from the group consisting of two-element compounds selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, and mixtures thereof; three-element compounds selected from the group consisting of GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, and mixtures thereof; and four-element compounds selected from the group consisting of GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, and mixtures thereof.
[0116] The IV-VI semiconductor compound is not particularly limited, and may be selected from the group consisting of binary compounds selected from the group consisting of SnS, SnSe, SnTe, PbS, PbSe, PbTe, and mixtures thereof; ternary compounds selected from the group consisting of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, and mixtures thereof; and quaternary compounds selected from the group consisting of SnPbSSe, SnPbSeTe, SnPbSTe, and mixtures thereof.
[0117] The Group IV element or compound is not particularly limited, but may be selected from the group consisting of mono-element compounds selected from the group consisting of Si, Ge, and mixtures thereof; and bi-element compounds selected from the group consisting of SiC, SiGe, and mixtures thereof.
[0118] Semiconductor nanoparticles (quantum dots) can have a homogeneous single structure or a core-shell double structure. The core and shell can contain different materials. The materials constituting each core and shell can be made of different semiconductor compounds. However, the energy band gap of the shell material is larger than that of the core material. Specifically, structures such as ZnTeSe / ZnSe / ZnS, InP / ZnSe / ZnS, CdSe / ZnS, and InP / ZnS are preferred.
[0119] For example, we will explain how to fabricate quantum dots with a core (CdSe)-shell (ZnS) structure. First, we add (CH 3 ) 2 Precursors for the core (CdSe), such as Cd(dimethylcadmium) and TOPSe(trioctylphosphine selenide), are injected to generate crystals. At this time, the crystals are maintained at high temperature for a certain time so that they grow to a certain size, and then the precursor for the shell (ZnS) is injected to form a shell on the surface of the already generated core. This allows the creation of CdSe / ZnS quantum dots capped with TOPO.
[0120] In the case of an OLED in which the light-emitting layer includes an organic metal complex, the light-emitting layer 150 may include, as a host material, for example, 6,9-diphenyl-9'-(5'-phenyl-[1,1':3',1"-terphenyl]-3-yl)3,3'-bi[9H-carbazole], 3,9-diphenyl-5-(3-(4-phenyl-6-(5'-phenyl-[1,1':3',1"-terphenyl]-3-yl)-1,3,5,-triazine-2-yl )phenyl)-9H-carbazole, 9,9'-diphenyl-3,3'-bi[9H-carbazole], tris(8-quinolinato)aluminium (Alq3), 4,4'-bis(carbazol-9-yl)biphenyl (CBP), poly(n-vinyl carbazole) carbazole (PVK), 9,10-di(naphthalene)anthracene (ADN), 4,4',4”-tris(N-carbazolyl)triphenylamine (TCTA), 1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene) 3-tert-butyl-9,10-di(naphth-2-yl)anthracene (TPBI), 3-tert-butyl-9,10-di(naphth-2-yl)anthracene (TBADN), distyrylarylene (DSA), 4,4'-bis(9-carbazole)2,2'-dimethyl-biphenyl (dmCBP), and the like.
[0121] The light-emitting layer 150 may contain, as a dopant material, for example, perylene and its derivatives, rubrene and its derivatives, coumarin and its derivatives, 4-dicyanomethylene-2-(pdimethylaminostyryl)-6-methyl-4H-pyran (DCM) and its derivatives, bis[2-(4,6-difluorophenyl)pyridinate]picolinate iridium(III):FIrpic, bis(1-phenylisoquinoline)(acetylacetonate)iridium(III):Ir(piq), 2 (acac)), tris(2-phenylpyridine)iridium(III):Ir(ppy) 3 ), iridium (Ir) complexes such as tris(2-(3-p-oxyyl)phenyl)pyridineiridium(III), osmium (Os) complexes, platinum complexes, etc. Of these, it is preferable that the light-emitting material is a light-emitting organometallic complex compound.
[0122] The method for forming the light-emitting layer is not particularly limited. It can be formed by applying a coating solution containing semiconductor nanoparticles or an organometallic complex (solution coating method). In this case, it is preferable to select a solvent that does not dissolve the material in the hole transport layer (hole transport material, especially copolymer) as the solvent constituting the coating solution.
[0123] An electron transport layer 160 is formed on the light emitting layer 150. The electron transport layer 160 is a layer having a function of transporting electrons, and is formed by using a vacuum deposition method, a spin coating method, an ink jet method, or the like. The electron transport layer 160 may be formed to a thickness of, for example, about 15 nm or more and about 50 nm or less.
[0124] The electron transport layer 160 may be formed of a known electron transport material. Examples of known electron transport materials include (8-quinolinolato) lithium (lithium quinolate) (Liq), tris(8-quinolinolato)aluminum (Alq), and the like. 3 ), and compounds having a nitrogen-containing aromatic ring. Specific examples of the compound having a nitrogen-containing aromatic ring include a compound having a pyridine ring such as 1,3,5-tri[(3-pyridyl)-phen-3-yl]benzene, a compound having a triazine ring such as 2,4,6-tris(3'-(pyridin-3-yl)biphenyl-3-yl)-1,3,5-triazine, and a compound having a 2-(4-(N-phenylbenzoyl)phenyl)-1,3,5-triazine. Examples of the electron transport material include compounds containing an imidazole ring such as 2-(4-(N-phenylbenzoimidazolyl-1-yl-phenyl)-9,10-dinaphthylanthracene and 1,3,5-tris(N-phenyl-benzimidazol-2-yl)benzene (TPBI). The above electron transport materials may be used alone or as a mixture of two or more kinds.
[0125] An electron injection layer 170 is formed on the electron transport layer 160. The electron injection layer 170 is a layer having a function of facilitating the injection of electrons from the second electrode 180. The electron injection layer 170 is formed by using a vacuum deposition method or the like. The electron injection layer 170 may be formed to a thickness of about 0.1 nm to about 5 nm, more specifically, about 0.3 nm to about 2 nm. Any known material can be used to form the electron injection layer 170. For example, the electron injection layer 170 can be formed using a lithium compound such as (8-quinolinato)lithium (Liq) and lithium fluoride (LiF), sodium chloride (NaCl), cesium fluoride (CsF), lithium oxide (Li 2 O), barium oxide (BaO), or the like.
[0126] The second electrode 180 is formed on the electron injection layer 170. The second electrode 180 is formed by using a vacuum deposition method or the like. The second electrode 180 is specifically a cathode, and is formed of a metal, an alloy, a conductive compound, or the like that has a small work function. For example, the second electrode 180 may be formed as a reflective electrode using a metal such as lithium (Li), magnesium (Mg), aluminum (Al), or calcium (Ca), or an alloy such as aluminum-lithium (Al-Li), magnesium-indium (Mg-In), or magnesium-silver (Mg-Ag). The second electrode 180 may be formed to a thickness of about 10 nm to about 200 nm, more specifically, about 50 nm to about 150 nm. Alternatively, the second electrode 180 may be formed of a thin film of 20 nm or less of the above metal materials, indium tin oxide (In 2 O 3 -SnO 2 ) and indium zinc oxide (In 2 O 3 Alternatively, the electrode may be formed as a transparent electrode using a transparent conductive film such as ZnO.
[0127] The EL element 100 according to this embodiment has been described above as an example of an electroluminescence element according to the present invention. The EL element 100 according to this embodiment can further improve durability (light-emitting life) by providing an organic film (particularly a hole transport layer or a hole injection layer) containing a copolymer. In addition, the light-emitting efficiency (current efficiency) can be further improved and the driving voltage can be reduced.
[0128] The laminated structure of the EL element 100 according to the present embodiment is not limited to the above example. The EL element 100 according to the present embodiment may be formed with other known laminated structures. For example, the EL element 100 may omit one or more layers among the hole injection layer 130, the hole transport layer 140, the electron transport layer 160, and the electron injection layer 170, or may additionally include other layers. Each layer of the EL element 100 may be formed as a single layer or as a multiple layer structure.
[0129] For example, the EL device 100 may further include a hole blocking layer between the hole transport layer 140 and the light emitting layer 150 in order to prevent excitons or holes from diffusing into the electron transport layer 160. The hole blocking layer may be formed of, for example, an oxadiazole derivative, a triazole derivative, or a phenanthroline derivative.
[0130] Furthermore, the copolymer according to the present embodiment can be applied to electroluminescence elements other than the above-mentioned QLED or OLED. The other electroluminescence elements to which the copolymer according to the present embodiment can be applied include, but are not limited to, organic-inorganic perovskite light-emitting elements, for example. EXAMPLES
[0131] The effects of the present invention will be described using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In the following examples, unless otherwise specified, the operations were performed at room temperature (25°C). In addition, unless otherwise specified, "%" and " "Parts" mean "% by mass" and "parts by mass" respectively.
[0132] [Example 1] (Synthesis of Monomer M-1) Monomer M-1 was synthesized according to the following reaction:
[0133] [ka]
[0134] In a 500mL four-neck flask, 2-bromo-9,9'-spirobi[9H-fluorene] (15.6g), 2-amino-9,9-dimethylfluorene (30.0g), 1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride dichloromethane adduct (3.09g), t-butoxy sodium (14.6g), and toluene (190mL) were placed and stirred for 4 hours at 100°C under a nitrogen atmosphere. The mixture was allowed to cool to room temperature (25°C, the same below), and insoluble matter was filtered off using Celite (registered trademark, the same below). The solvent was removed from the filtrate under reduced pressure, and the residue was purified by column chromatography to obtain N-(9,9'-dimethyl-9H-fluoren-2-yl)-9,9'-spirobi[fluorene]-2-amine (33.4 g, yield 84.0%).
[0135] In a 2L four-neck flask, 3,6-dichlorocarbazole (100.0 g), 4-bromo-4'-iodobiphenyl (167 g), copper iodide (4.03 g), sodium t-butoxide (81.4 g), trans-1,2-cyclohexanediamine (9.67 g), and 1,4-dioxane (1060 mL) were placed and heated and stirred at 100°C for 4 hours under a nitrogen atmosphere. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed under reduced pressure and dissolved in toluene (800 mL). The solution was washed with water (1 L), 2N-HCl (500 mL x 2), and water (500 mL x 2), and then diluted with MgSO 4 The solution was filtered using Celite and silica gel. The solvent was removed under reduced pressure, and the residue was recrystallized using a mixed solvent of toluene and ethanol, and then dried to obtain 9-(4'bromo-[1,1'-biphenyl]-4-yl)-3,6-dichloro-9H-carbazole (81.5 g, 74.8%).
[0136] In a 500 mL four-neck flask, N-(9,9'-dimethyl-9H-fluoren-2-yl)-9,9'-spirobi[fluoren]-2-amine (8.00 g), 9-(4'bromo-[1,1'-biphenyl]-4-yl)-3,6-dichloro-9H-carbazole (7.13 g), palladium acetate (Pd(OAc) 2 ) (0.171g), tri-tert-butylphosphonium tetrafluoroborate (t-Bu 3 P.B.F. 4) (0.332 g), sodium t-butoxide (2.93 g), and toluene (150 mL) were added and stirred at 100°C for 3 hours under a nitrogen atmosphere. Insoluble matter was filtered off using Celite, activated carbon (3 g) and zeolite (3 g) were added, and the mixture was stirred at 110°C for 30 minutes. Solids were filtered off using Celite, and the filtrate was passed through silica gel. The solvent was distilled off under reduced pressure, and the residue was purified using column chromatography (silica gel, hexane / toluene), and further recrystallized and dried using a mixed solvent of toluene and acetonitrile to obtain N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-N-(9,9'-dimethyl-9H-fluoren-2-yl)-9,9'-spirobi[fluorene]-2-amine (6.57 g, 76.0%).
[0137] In a 200 mL four-neck flask, add 6.56 g of N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-N-(9,9'-dimethyl-9H-fluoren-2-yl)-9,9'-spirobi[fluorene]-2-amine, 6.79 g of bis-pinacol diborate, 6.25 g of potassium acetate, and palladium tris(dibenzylideneacetone) (Pd 2 (dba) 3 ) (0.48 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.754 g), and 1,4-dioxane (160 mL) were added and refluxed under nitrogen atmosphere for 4 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was removed under reduced pressure, and the residue was dissolved in toluene (100 mL), and activated carbon (2 g) and zeolite (2 g) were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, and the filtrate was passed through silica gel. The solvent was removed under reduced pressure, and the residue was recrystallized from a mixed solvent of toluene and hexane, and then dried to obtain monomer M-1 (6.84 g, 59.3%).
[0138] (Synthesis of copolymer P-1) Under a nitrogen atmosphere, monomer M-1 (1.15 g), 2,7-dibromo-9,9-dioctylfluorene (0.581 g), palladium acetate (2.40 mg), tris(2-methoxyphenyl)phosphine (19.3 mg), toluene (35 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (5.46 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Phenylboronic acid (128 mg), bis(triphenylphosphine)palladium(II) dichloride (44.6 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (5.46 g) were added and stirred at 85 ° C for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (3.58 g) dissolved in ion-exchanged water (35 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-1 (0.89 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=15,700 and Mw / Mn=1.60.
[0139] Copolymer P-1 is presumed to have the following structural units based on the monomer charge ratio.
[0140] [ka]
[0141] (Fabrication of quantum dot electroluminescence element D-1) A glass substrate with indium tin oxide (ITO) patterned to a thickness of 150 nm was used as the first electrode (anode). This glass substrate with ITO was washed sequentially with a neutral detergent, deionized water, water, and isopropyl alcohol, and then subjected to UV-ozone treatment. Next, poly(3,4-ethylenedioxythiophene) / poly(4-styrenesulfonate) (PEDOT / PSS) (Sigma-Aldrich) was applied to the glass substrate with ITO by spin coating so that the dry thickness was 30 nm, and then dried. As a result, a hole injection layer with a thickness (dry thickness) of 30 nm was formed on the glass substrate with ITO.
[0142] A 1.0% by mass toluene solution of copolymer P-1 (hole transport material) was applied onto the hole injection layer by spin coating so that the dry thickness was 30 nm, and then heat-treated at 230° C. for 60 minutes to form a hole transport layer. As a result, a hole transport layer having a thickness (dry thickness) of 30 nm was formed on the hole injection layer.
[0143] In cyclohexane, the following structure:
[0144] [ka]
[0145] A quantum dot dispersion liquid was prepared by dispersing blue quantum dots of ZnTeSe / ZnSe / ZnS (core / shell / shell; average diameter = about 10 nm) having the above structure to a concentration of 1.0 mass %. The hole transport layer (particularly copolymer P-1) does not dissolve in cyclohexane. This quantum dot dispersion liquid was applied to the hole transport layer by spin coating so that the dry film thickness was 30 nm, and then dried. As a result, a quantum dot light-emitting layer having a thickness (dry film thickness) of 30 nm was formed on the hole transport layer. The light emitted by irradiating the quantum dot dispersion liquid with ultraviolet light had a central wavelength of 462 nm and a half-width of 30 nm.
[0146] This quantum dot light-emitting layer was completely dried. On this quantum dot light-emitting layer, lithium quinolate (Liq) and 1,3,5-tris(N-phenylbenzimidazol-2-yl)benzene (TPBI) (Sigma-Aldrich) as an electron transport material were co-deposited using a vacuum deposition apparatus. As a result, an electron transport layer with a thickness of 36 nm was formed on the quantum dot light-emitting layer.
[0147] Using a vacuum deposition apparatus, (8-quinolinolato)lithium (lithium quinolate) (Liq) was deposited on the electron transport layer, resulting in the formation of an electron injection layer having a thickness of 0.5 nm on the electron transport layer.
[0148] Aluminum (Al) was deposited on the electron injection layer using a vacuum deposition apparatus. As a result, a second electrode (cathode) having a thickness of 100 nm was formed on the electron injection layer. This resulted in the quantum dot electroluminescence device D-1.
[0149] [Example 2] (Synthesis of Monomer M-2) Monomer M-2 was synthesized according to the following reaction:
[0150] [ka]
[0151] In a 500 mL four-neck flask, 2-(4-biphenyl)amino-9,9-dimethylfluorene (10.0 g), 9-(4'bromo-[1,1'-biphenyl]-4-yl)-3,6-dichloro-9H-carbazole (12.9 g), palladium acetate (Pd(OAc) 2 ) (0.311g), tri-tert-butylphosphonium tetrafluoroborate (t-Bu 3 P.B.F. 4) (0.602 g), sodium t-butoxide (5.31 g), and toluene (280 mL) were added and stirred at 100°C for 5 hours under a nitrogen atmosphere. Insoluble matter was filtered off using Celite, and activated carbon (3 g) and zeolite (3 g) were added and stirred at 110°C for 30 minutes. Solids were filtered off using Celite, and the filtrate was passed through silica gel. The solvent was removed under reduced pressure, and the residue was purified using column chromatography (silica gel, hexane / toluene) to obtain N-([1,1'-biphenyl]-4-yl)-N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-9,9'-dimethyl-9H-fluoren-2-amine (18.5 g, 89.4%).
[0152] In a 200 mL four-neck flask, add N-([1,1'-biphenyl]-4-yl)-N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-9,9'-dimethyl-9H-fluoren-2-amine (10.0 g), bis-pinacol diborate (8.52 g), potassium acetate (7.92 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.695 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.950 g), and 1,4-dioxane (110 mL) were added and refluxed under nitrogen atmosphere for 4 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was removed under reduced pressure, and the residue was dissolved in toluene (100 mL), and activated carbon (3 g) and zeolite (3 g) were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, the filtrate was passed through silica gel, the solvent was removed under reduced pressure, and the residue was recrystallized from a mixed solvent of toluene and hexane, and dried to obtain monomer M-2 (6.09 g, 48.9%).
[0153] (Synthesis of copolymer P-2) Under a nitrogen atmosphere, monomer M-2 (1.57 g), 2,7-dibromo-9,9-dioctylfluorene (0.927 g), palladium acetate (3.8 mg), tris(2-methoxyphenyl)phosphine (30.9 mg), toluene (54 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (8.71 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Phenylboronic acid (204 mg), bis(triphenylphosphine)palladium(II) dichloride (71.1 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (8.71 g) were added and stirred at 85 ° C for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.71 g) dissolved in ion-exchanged water (54 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-2 (0.63 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=52,300 and Mw / Mn=2.76.
[0154] Copolymer P-2 is presumed to have the following structural units based on the monomer charge ratio.
[0155] [ka]
[0156] (Fabrication of quantum dot electroluminescence element D-2) In Example 1 (preparation of quantum dot electroluminescence element D-1), the same procedure was carried out except that copolymer P-2 was used instead of copolymer P-1, to prepare quantum dot electroluminescence element D-2.
[0157] [Example 3] (Synthesis of Monomer M-3) Monomer M-3 was synthesized according to the following reaction:
[0158] [ka]
[0159] In a 500 mL four-neck flask, 2-(3-biphenylyl)amino-9,9-dimethylfluorene (5.00 g), 9-(4'bromo-[1,1'-biphenyl]-4-yl)-3,6-dichloro-9H-carbazole (12.9 g), palladium acetate (Pd(OAc) 2 ) (0.156g), tri-tert-butylphosphonium tetrafluoroborate (t-Bu 3 P.B.F. 4 ) (0.150 g), sodium t-butoxide (2.65 g), and toluene (140 mL) were added and stirred at 100°C for 5 hours under a nitrogen atmosphere. Insoluble matter was filtered off using Celite, activated carbon (5.0 g) and zeolite (5.0 g) were added, and the mixture was stirred at 110°C for 30 minutes. Solids were filtered off using Celite, and the filtrate was passed through silica gel. The solvent was removed under reduced pressure, and the residue was purified using column chromatography (silica gel, hexane / toluene) to obtain N-([1,1'-biphenyl]-4-yl)-N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-9,9'-dimethyl-9H-fluoren-2-amine (9.18 g, 88.8%).
[0160] In a 200 mL four-neck flask, add N-([1,1'-biphenyl]-4-yl)-N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-9,9'-dimethyl-9H-fluoren-2-amine (9.00 g), bis-pinacol diborate (7.64 g), potassium acetate (7.08 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3) (0.551 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.860 g), and 1,4-dioxane (100 mL) were added and refluxed under nitrogen atmosphere for 4 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was removed under reduced pressure, and the residue was dissolved in toluene (100 mL), and activated carbon (3 g) and zeolite (3 g) were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, and the filtrate was passed through silica gel. The solvent was removed under reduced pressure, and the residue was recrystallized from a mixed solvent of toluene and hexane, and then dried to obtain monomer M-3 (6.94 g, 62.0%).
[0161] (Synthesis of copolymer P-3) Under a nitrogen atmosphere, monomer M-3 (1.39 g), 2,7-dibromo-9,9-dioctylfluorene (0.824 g), palladium acetate (3.4 mg), tris(2-methoxyphenyl)phosphine (31.7 mg), toluene (44 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.74 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Phenylboronic acid (181 mg), bis(triphenylphosphine)palladium (II) dichloride (63.2 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.74 g) were added and stirred at 85 ° C for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.07 g) dissolved in ion-exchanged water (44 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-3 (0.83 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=33,300 and Mw / Mn=2.19.
[0162] Copolymer P-3 is presumed to have the following structural units based on the monomer charge ratio.
[0163] [ka]
[0164] (Fabrication of quantum dot electroluminescence element D-3) In Example 1 (preparation of quantum dot electroluminescence element D-1), the same procedure was carried out except that copolymer P-3 was used instead of copolymer P-1, to prepare quantum dot electroluminescence element D-3.
[0165] [Example 4] (Synthesis of Monomer M-4) Monomer M-4 was synthesized according to the following reaction:
[0166] [ka]
[0167] In a 500 mL four-neck flask, 2-(2-biphenylyl)amino-9,9-dimethylfluorene (12.0 g), 9-(4'bromo-[1,1'-biphenyl]-4-yl)-3,6-dichloro-9H-carbazole (15.5 g), palladium acetate (Pd(OAc) 2 ) (0.372 g), tri-tert-butylphosphonium tetrafluoroborate (t-Bu 3 P.B.F. 4) (0.722 g), sodium t-butoxide (6.38 g), and toluene (330 mL) were added and stirred at 100°C for 1 hour under a nitrogen atmosphere. Insoluble matter was filtered off using Celite, and activated carbon (6.0 g) and zeolite (6.0 g) were added and stirred at 110°C for 30 minutes. Solids were filtered off using Celite, and the filtrate was passed through silica gel. The solvent was removed under reduced pressure, and the residue was purified using column chromatography (silica gel, hexane / toluene) to obtain N-([1,1'-biphenyl]-2-yl)-N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-9,9'-dimethyl-9H-fluoren-2-amine (18.2 g, 73.4%).
[0168] In a 200 mL four-neck flask, add N-([1,1'-biphenyl]-2-yl)-N-(4'-(3,6-dichloro-9H-carbazol-9-yl)-[1,1'-biphenyl]-4-yl)-9,9'-dimethyl-9H-fluoren-2-amine (9.00 g), bis-pinacol diborate (7.64 g), potassium acetate (7.08 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.551 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.860 g), and 1,4-dioxane (100 mL) were added and refluxed under nitrogen atmosphere for 4 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was removed under reduced pressure, and the residue was dissolved in toluene (100 mL), and activated carbon (3 g) and zeolite (3 g) were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, and the filtrate was passed through silica gel. The solvent was removed under reduced pressure, and the residue was recrystallized from a mixed solvent of toluene and hexane, and then dried to obtain monomer M-4 (7.88 g, 63.5%).
[0169] (Synthesis of copolymer P-4) Under an argon atmosphere, monomer M-4 (1.57 g), 2,7-dibromo-9,9-di-n-octylfluorene (0.927 g), palladium acetate (3.8 mg), tris(2-methoxyphenyl)phosphine (30.9 mg), toluene (50 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (8.71 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (204 mg), dichlorobis(triphenylphosphine)palladium (71.1 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (8.71 g) were added and stirred for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.71 g) dissolved in ion-exchanged water (50 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass acetic acid aqueous solution, and water. The organic layer was passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-4 (0.76 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=72,700 and Mw / Mn=3.45.
[0170] Copolymer P-4 is presumed to have the following structural units based on the monomer charge ratio.
[0171] [ka]
[0172] (Fabrication of quantum dot electroluminescence element D-4) In Example 1 (preparation of quantum dot electroluminescence element D-1), the same procedure was carried out except that copolymer P-4 was used instead of copolymer P-1, to prepare quantum dot electroluminescence element D-4.
[0173] [Example 5] (Synthesis of copolymer P-5) Under an argon atmosphere, monomer M-4 (1.42 g), 2,7-dibromo-9,9-didodecylfluorene (1.01 g), palladium acetate (3.4 mg), tris(2-methoxyphenyl)phosphine (27.9 mg), toluene (50 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.88 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (185 mg), dichlorobis(triphenylphosphine)palladium (64.4 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.88 g) were added and stirred for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.17 g) dissolved in ion-exchanged water (50 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass acetic acid aqueous solution, and water. The organic layer was passed through a column chromatography filled with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-5 (0.44 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=30,000 and Mw / Mn=2.29.
[0174] Copolymer P-5 is presumed to have the following structural units based on the monomer charge ratio.
[0175] [ka]
[0176] (Fabrication of quantum dot electroluminescence element D-5) In Example 1 (preparation of quantum dot electroluminescence element D-1), the same procedure was carried out except that copolymer P-5 was used instead of copolymer P-1, to prepare quantum dot electroluminescence element D-5.
[0177] [Example 6] (Synthesis of Monomer M-5) Monomer M-5 was synthesized according to the following reaction:
[0178] [ka]
[0179] In a 500 mL four-neck flask, 3-chloro-9H-carbazole (10.0 g), 4-hexylbromobenzene (13.2 g), sodium t-butoxide (t-BuONa) (7.15 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3 ) (0.91g), tri-tert-butylphosphonium tetrafluoroborate (t-Bu 3 P.B.F. 4 ) (0.58 g) and toluene (169 mL) were added, and the mixture was refluxed at 100°C for 10 hours under a nitrogen atmosphere. The reaction solution was cooled to room temperature, and the solvent was distilled off under reduced pressure. The residue was purified using column chromatography (silica gel, hexane / toluene) to obtain 3-chloro-9-(4-hexylphenyl)-9H-carbazole (15.2 g, 83%).
[0180] In a 500 mL four-neck flask, 3-chloro-9-(4-hexylphenyl)-carbazole (15.0 g), bis-pinacol diborate (15.8 g), potassium acetate (5.97 g), tris(dibenzylideneacetone)dipalladium (Pd 2 (dba) 3) (0.76 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.79 g), and 1,4-dioxane (145 mL) were added and refluxed under nitrogen atmosphere for 8 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was removed under reduced pressure, and the residue was dissolved in toluene (50 mL), and activated carbon (1.5 g) and zeolite (1.5 g) were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, the filtrate was passed through silica gel, the solvent was removed under reduced pressure, and the residue was recrystallized with a mixed solvent of toluene and acetonitrile, and dried to obtain 9-(4-hexylphenyl)-3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-9H-carbazole (13.1 g, 70%).
[0181] In a 1L four-neck flask, 3,6-dichloro-9H-carbazole (50.0 g), p-bromoiodobenzene (72.4 g), copper iodide (2.02 g), t-butoxy sodium (30.5 g), trans-1,2-cyclohexanediamine (2.42 g), and 1,4-dioxane (423 mL) were placed and heated and stirred at 100°C for 12 hours under a nitrogen atmosphere. The mixture was allowed to cool to room temperature, and insoluble matter was filtered off using Celite. The solvent was removed under reduced pressure and dissolved in toluene (400 mL). The solution was washed with water (500 mL), 2N-HCl (300 mL x 2), and water (300 mL x 2), and then diluted with MgSO 4 The solvent was removed under reduced pressure, and the residue was recrystallized from a mixed solvent of tetrahydrofuran and ethanol and then dried to obtain 9-(4-bromophenyl)-3,6-dichloro-9H-carbazole (56.6 g, 68.4%).
[0182] In a 500 mL four-neck flask, 9-(4-hexylphenyl)-3-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-9H-carbazole (10.0 g), 9-(4-bromophenyl)-3,6-dichloro-9H-carbazole (8.63 g), sodium carbonate (3.51 g), tetrakis(triphenylphosphine)palladium (Pd(PPh) 3) (1.27 g), toluene (45 mL), ethanol (55 mL), and distilled water (55 mL) were added and refluxed under nitrogen atmosphere for 4 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The filtrate was passed through silica gel, and the solvent was distilled off under reduced pressure. The residue was recrystallized from a mixed solvent of toluene and methanol, and then dried to obtain 3,6-dichloro-9-(4-(9-(4-hexylphenyl)-9H-carbazol-3-yl)phenyl)-9H-carbazole (11.9 g, 84.4%). In a 500 mL four-neck flask, 3,6-dichloro-9-(4-(9-(4-hexylphenyl)-9H-carbazol-3-yl)phenyl)-9H-carbazole (10.0 g), bispinacol diborate (15.9 g), potassium acetate (9.04 g), palladium acetate (0.352 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.748 g), and 1,4-dioxane (157 mL) were placed and refluxed under nitrogen atmosphere for 4 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was removed under reduced pressure, and the residue was dissolved in toluene (200 mL), and activated carbon (3 g) and zeolite (3 g) were added, followed by stirring at 130°C for 30 minutes. The solid was filtered off using Celite, and the filtrate was passed through silica gel. The solvent was distilled off under reduced pressure, and the residue was recrystallized from a mixed solvent of toluene and acetonitrile, and then dried to obtain monomer M-5 (7.68 g, 59.5%).
[0183] (Synthesis of copolymer P-6) Under an argon atmosphere, monomer M-5 (1.72 g), 2,7-dibromo-9,9-dioctylfluorene (1.152 g), palladium acetate (4.7 mg), tris(o-tolyl)phosphine (38.1 mg), toluene (57 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (10.8 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (253 mg), dichlorobis(triphenylphosphine)palladium (88.0 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (10.8 g) were added and stirred for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (7.06 g) dissolved in ion-exchanged water (60 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass hydrochloric acid aqueous solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-6 (1.01 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=16,500 and Mw / Mn=1.53.
[0184] Copolymer P-6 is presumed to have the following structural units based on the monomer charge ratio.
[0185] [ka]
[0186] (Fabrication of quantum dot electroluminescence element D-6) In Example 1 (preparation of quantum dot electroluminescence element D-1), the same procedure was carried out except that copolymer P-6 was used instead of copolymer P-1, to prepare quantum dot electroluminescence element D-6.
[0187] [Example 7] (Synthesis of Monomer M-6) Monomer M-6 was synthesized according to the following reaction:
[0188] [ka]
[0189] In a 300 mL four-neck flask, 9,9'-spirobi[9H-fluorene]-2-amine (14.0 g), 1-bromodibenzofuran (10.4 g), sodium t-butoxide (t-BuONa) (11.4 g), [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride dichloromethane adduct (PdCl 2 (dppf)CH 2 Cl 2 ) (1.71 g) and toluene (105 mL) were added and refluxed at 100°C for 2 hours under a nitrogen atmosphere. The reaction solution was cooled to room temperature and the solvent was distilled off under reduced pressure. The resulting solid was dispersed in methanol (400 mL), stirred for 1 hour, and filtered. The resulting solid was washed with water (300 mL) and methanol (300 mL), recrystallized from a mixed solvent of toluene and hexane, and dried to obtain N-(9,9'-spirobi[fluoren]-2-yl)dibenzo[d,b]furan-1-amine (6.69 g, 31.8%).
[0190] In a 300 mL four-neck flask, N-(9,9'-spirobi[fluoren]-2-yl)dibenzo[d,b]furan-1-amine (6.00 g), 9-(4'bromo-[1,1'-biphenyl]-4-yl)3,6-dichloro-9H-carbazole (5.63 g), palladium acetate (Pd(OAc) 2 ) (0.135g), tri-tert-butylphosphonium tetrafluoroborate (t-Bu 3 P.B.F. 4) (0.262 g), sodium t-butoxide (2.31 g), and toluene (120 mL) were added and stirred at 100°C for 3 hours under a nitrogen atmosphere. Insoluble matter was filtered off using Celite, and activated carbon (3.0 g) and zeolite (3.0 g) were added and stirred at 110°C for 30 minutes. Solids were filtered off using Celite, and the filtrate was passed through silica gel. The solvent was distilled off under reduced pressure, and the residue was purified using column chromatography (silica gel, hexane / toluene) to obtain N-(9,9'-spirobi[fluoren]-2-yl)-N-(4'-(3,6-dichloro-9H-yl)-[1,1'-biphenyl]-4-yl)dibenzo[d,b]furan-1-amine) (7.40 g, 69.4%).
[0191] In a 200 mL four-neck flask, add 5.00 g of N-(9,9'-spirobi[fluoren]-2-yl)-N-(4'-(3,6-dichloro-9H-yl)-[1,1'-biphenyl]-4-yl)dibenzo[d,b]furan-1-amine, 4.31 g of bis-pinacol diborate, 3.33 g of potassium acetate, and palladium tris(dibenzylideneacetone) (Pd 2 (dba) 3 ) (0.259 g), 2-dicyclohexylphosphino-2',4',6'-triisopropylbiphenyl (XPhos) (0.404 g), and 1,4-dioxane (45 mL) were added and refluxed under nitrogen atmosphere for 4 hours. The reaction solution was cooled to room temperature, and the solid was filtered off using Celite. The solvent was removed under reduced pressure, and the residue was dissolved in toluene (100 mL), and activated carbon (3 g) and zeolite (3 g) were added, and the mixture was stirred at 130°C for 30 minutes. The solid was filtered off using Celite, and the filtrate was passed through silica gel. The solvent was removed under reduced pressure, and the residue was recrystallized from a mixed solvent of toluene and acetonitrile, and then dried to obtain monomer M-6 (3.05 g, 50.5%).
[0192] (Synthesis of copolymer P-7) Under an argon atmosphere, monomer M-6 (1.42 g), 2,7-dibromo-9,9-dioctylfluorene (0.822 g), palladium acetate (3.4 mg), tris(2-methoxyphenyl)phosphine (27.7 mg), toluene (55 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.81 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (183 mg), dichlorobis(triphenylphosphine)palladium (63.1 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (7.81 g) were added and stirred for 6 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (5.17 g) dissolved in ion-exchanged water (50 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the aqueous layer, the organic layer was washed with water, a 3% by mass acetic acid aqueous solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-7 (0.81 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=69,900 and Mw / Mn=2.12.
[0193] Copolymer P-7 is presumed to have the following structural units based on the monomer charge ratio.
[0194] [ka]
[0195] (Preparation of quantum dot electroluminescence element D-7) In Example 1 (preparation of quantum dot electroluminescence element D-1), the same procedure was carried out except that copolymer P-7 was used instead of copolymer P-1, to prepare quantum dot electroluminescence element D-7.
[0196] [Comparative Example 1] (Fabrication of quantum dot electroluminescence element D-8) A quantum dot electroluminescence device D-8 was produced in the same manner as in Example 1 (preparation of quantum dot electroluminescence device D-1), except that poly[(9,9-dioctylfluorenyl-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine)](TFB) (manufactured by Luminescence Technology Corp.) having the following structural unit was used instead of the copolymer P-1. The weight average molecular weight (Mw) and dispersity (Mw / Mn) of TFB were measured by SEC. As a result, the weight average molecular weight (Mw) and dispersity (Mw / Mn) of TFB were 359,000 and 3.40, respectively.
[0197] [ka]
[0198] [Comparative Example 2] (Synthesis of Monomer M-7) Monomer M-7 was synthesized according to the following reaction:
[0199] [ka]
[0200] In a 500 mL three-neck flask, 9-[4-(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)phenyl]-9H-carbazole (5.34 g), 4,4'-dibromo-4"-iodotriphenylamine (7.50 g), sodium carbonate (2.69 g), tetrakis(triphenylphosphine)palladium(0) (Pd(PPh 3 ) 4 ) (0.74 g), 1,4-dioxane (125 mL), and water (63 mL) were added and stirred at 100 °C for 3 hours under a nitrogen atmosphere. The mixture was cooled to room temperature, toluene (125 mL) was added, and the mixture was washed with water (50 mL x 3), and then MgSO 4The mixture was dried at 40° C. The solvent was removed under reduced pressure, and the mixture was dissolved in toluene (50 mL) and hexane (100 mL), and activated carbon (8 g) was added and refluxed for 30 minutes. The mixture was cooled to room temperature, and the activated carbon was filtered off using Celite, and the solvent was removed under reduced pressure. The residue was subjected to column chromatography and recrystallization (toluene / acetone) to obtain monomer M-7 (6.38 g).
[0201] (Synthesis of copolymer P-8) Under an argon atmosphere, monomer M-7 (1.47), 2,7-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolan-2-yl)-9,9-di-N-octylfluorene (1.47 g), palladium acetate (5.1 mg), tris(2-methoxyphenyl)phosphine (48.4 mg), toluene (59 mL), and 20% by mass tetraethylammonium hydroxide aqueous solution (9.98 g) were added to a four-neck flask and stirred at 85 ° C for 6 hours. Next, phenylboronic acid (242 mg), tetrakis(triphenylphosphino)palladium (52.9 mg), and 20% by mass tetraethylammonium hydroxide aqueous solution (9.98 g) were added and stirred for 3 hours. Then, sodium N,N-diethyldithiocarbamate trihydrate (7.74 g) dissolved in ion-exchanged water (59 mL) was added and stirred at 85 ° C for 2 hours. After separating the organic layer from the water layer, the organic layer was washed with water, 3% by mass aqueous acetic acid solution, and water. The organic layer was passed through a column chromatography packed with silica gel / alumina, and the solvent was distilled off under reduced pressure. The resulting liquid was dropped into methanol, and the precipitated solid was dissolved in toluene, and dropped into methanol to precipitate. The precipitated solid was filtered and dried to obtain copolymer P-8 (0.788 g). The weight average molecular weight and dispersity of the obtained copolymer were measured by SEC, and found to be Mw=74,000 and Mw / Mn=2.45.
[0202] Copolymer P-8 is presumed to have the following structural units based on the monomer charge ratio.
[0203] [ka]
[0204] (Preparation of quantum dot electroluminescence element D-9) In Example 1 (preparation of quantum dot electroluminescence element D-1), except that copolymer P-8 was used instead of copolymer P-1, the same procedure was carried out to prepare quantum dot electroluminescence element D-9.
[0205] <Evaluation> [Copolymer properties] For each copolymer, the HOMO level (eV), LUMO level (eV) and glass transition temperature (Tg) (° C.) were measured by the following method. The results are shown in Table 1 below.
[0206] (HOMO level measurement) Each copolymer was dissolved in xylene to a concentration of 1% by mass to prepare a coating solution. The coating solution prepared above was used to form a film on a UV-cleaned glass substrate with ITO by spin coating at a rotation speed of 2000 rpm, and then dried on a hot plate at 150°C for 30 minutes to prepare a sample for measurement. The HOMO level of the sample was measured using an atmospheric photoelectron spectrometer (AC-3, manufactured by Riken Keiki Co., Ltd.). At this time, the tangent intersection point of the rising edge was calculated from the measurement results and used as the HOMO level (eV). The HOMO level is usually a negative value.
[0207] (LUMO level measurement) Each copolymer was dissolved in toluene to a concentration of 3.2% by mass to prepare a coating solution. Using the coating solution prepared above, a film was formed by spin coating at a rotation speed of 1600 rpm on a UV-cleaned glass substrate with ITO, and then dried on a hot plate at 250°C for 60 minutes to prepare a sample for measurement (film thickness: about 70 nm). The obtained sample was cooled to 77K (-196°C) and the photoluminescence (PL) spectrum was measured. The LUMO level (eV) was calculated from the peak value on the shortest wavelength side of the PL spectrum.
[0208] (Glass transition temperature (Tg)) Each copolymer was measured using a differential scanning calorimeter (DSC) (Seiko Instruments Inc., product name: DSC6000) by heating the sample to 300°C at a heating rate of 10°C / min and holding it for 10 minutes, then cooling it to 25°C at a heating rate of 10°C / min and holding it for 10 minutes, and then heating it to 300°C at a heating rate of 10°C / min. After the measurement, the sample was cooled to room temperature (25°C) at a rate of 10°C / min.
[0209] [Table 1]
[0210] [Evaluation of quantum dot electroluminescence devices] The luminous efficiency and luminous lifetime of each quantum dot electroluminescence device were evaluated by the following methods. The results are shown in Table 2 below.
[0211] (Luminous efficiency) When a voltage is applied to each quantum dot electroluminescence element, a current begins to flow at a certain voltage, and the quantum dot electroluminescence element emits light. Using a DC constant voltage power supply (Keyence, source meter), the voltage was gradually increased for each element, the current value at that time was measured, and the luminance during emission was measured using a luminance measuring device (Topcom, SR-3). The measurement was stopped when the luminance began to decay. The current value per unit area (current density) was calculated from the area of each element, and the luminance (cd / m 2 ) to current density (A / m 2 ) to calculate the current efficiency (cd / A). The highest current efficiency in the measured voltage range was taken as "cd / A max." Note that current efficiency indicates the efficiency of converting current into luminous energy (conversion efficiency), and the higher the current efficiency, the higher the performance of the element.
[0212] When a voltage is applied to each quantum dot electroluminescence element using a DC constant voltage power supply (Keyence, source meter), a current starts to flow at a constant voltage, and the quantum dot electroluminescence element emits light. 2 The voltage (V) at this point was defined as the driving voltage "V@5mA".
[0213] In addition, the external quantum efficiency (EQE) (%) at cd / A max was calculated from the spectral radiance spectrum measured by a luminance measuring device, assuming Lambertian radiation, and the luminous efficiency was evaluated.
[0214] (Light Emitting Life) A DC constant voltage power supply (Keyence Corporation, source meter) was used to apply a predetermined voltage to each quantum dot electroluminescence element, causing the quantum dot electroluminescence element to emit light. While measuring the emission of the quantum dot electroluminescence element with a luminance measuring device (Topcom Corporation, SR-3), the current was gradually increased until the luminance reached 650 nit (cd / m 2 ), the current was made constant and left as is. The luminance value measured by the luminance measuring device gradually decreased, and the time it took for the luminance to reach 90% of the initial luminance was taken as "LT90(hr)", and the time it took for the luminance to reach 50% of the initial luminance was taken as "LT50(hr)".
[0215] [Table 2]
[0216] From the results of Table 2 above, it was shown that the quantum dot electroluminescence element of the embodiment can exhibit significantly higher luminous efficiency and durability (especially luminous life) than the quantum dot electroluminescence element of the comparative example. In this example, a blue quantum dot electroluminescence element was evaluated, but it is considered that the same results as above can be obtained with a red quantum dot electroluminescence element, etc.
[0217] Although the present invention has been described above with reference to embodiments and examples, the present invention is not limited to the specific embodiments and examples, and various modifications and changes are possible within the scope of the invention described in the claims. [Explanation of symbols]
[0218] 100...Electroluminescence element (EL element), 110...substrate, 120...first electrode, 130...hole injection layer, 140...hole transport layer, 150...light-emitting layer, 160...electron transport layer, 170...electron injection layer, 180...Second electrode.
Claims
1. A copolymer having a structural unit represented by the following formula (1): 【Chemistry 1】 In formula (1), X is a single bond, -L 1 - or -L 1 -L 1 -, where L 1 each independently represents a substituted or unsubstituted divalent aromatic hydrocarbon group having 6 to 25 carbon atoms, L 2 represents a substituted or unsubstituted aromatic hydrocarbon group having 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having 3 to 25 ring atoms, Ar 1 and Ar 2 each independently represents a substituted or unsubstituted aromatic hydrocarbon group having from 6 to 25 carbon atoms, or a substituted or unsubstituted aromatic heterocyclic group having from 3 to 25 ring atoms, Y represents a substituted or unsubstituted divalent aromatic hydrocarbon group having from 6 to 60 carbon atoms, or a substituted or unsubstituted divalent aromatic heterocyclic group having from 3 to 60 ring atoms; At this time, L 2 , Ar 1 and Ar 2 satisfies at least one of the following conditions (i) and (ii): (i) Ar 1 and Ar 2 represent different groups; (ii) L 2 and Ar 1 form a ring with each other.
2. In the formula (1), L 2 , Ar 1 and Ar 2 satisfies the above condition (i), and Ar 1 and Ar 2 The copolymer according to claim 1 , wherein each independently represents a group selected from the following group: 【Chemistry 2】 Here, each R independently represents a hydrogen atom or a linear or branched hydrocarbon group having 1 to 14 carbon atoms.
3. In the formula (1), L 2 The copolymer according to claim 1 or 2, wherein represents a group selected from the following group: 【Chemistry 3】 Here, * represents a bond to the nitrogen atom of the carbazole ring in the main chain.
4. In the formula (1), L 2 , Ar 1 and Ar 2 satisfies the above condition (ii), and -L 2 -N(Ar 1 ) (Ar 2 3. The copolymer of claim 2, wherein: 【Chemistry 4】 However, Ar 2 has the same definition as in formula (1).
5. In the formula (1), Ar 2 The copolymer according to claim 4, wherein represents a group selected from (2-1) to (2-24).
6. The copolymer according to any one of claims 1 to 5, wherein in the formula (1), Y represents a group selected from the following group: 【Chemistry 5】 However, R 1 , R 2 and R 4 each independently represents a hydrogen atom, a linear or branched saturated hydrocarbon group having from 1 to 14 carbon atoms, or an aromatic hydrocarbon group having from 6 to 28 carbon atoms; R 3 each independently represents a linear or branched saturated hydrocarbon group having 1 to 14 carbon atoms.
7. The copolymer according to claim 6, wherein in the formula (1), Y represents a group selected from the groups (5-1) to (5-7).
8. The copolymer according to any one of claims 1 to 7, At least a solvent or dispersion medium; A liquid composition comprising:
9. A thin film comprising the copolymer according to any one of claims 1 to 7.
10. An electroluminescence device material comprising the copolymer according to any one of claims 1 to 7.
11. An electroluminescence element comprising a first electrode, a second electrode, and one or more organic films disposed between the first electrode and the second electrode, An electroluminescence device, wherein at least one layer of the organic film comprises the copolymer according to any one of claims 1 to 7.
12. The electroluminescence device according to claim 11, wherein the organic film containing the copolymer is a hole transport layer or a hole injection layer.
13. 13. The electroluminescence device according to claim 11, wherein the organic film has a light-emitting layer containing semiconductor nanoparticles or an organometallic complex.
14. A method for manufacturing an electroluminescent element comprising a pair of electrodes and one or more organic films disposed between the electrodes and containing a copolymer described in any one of claims 1 to 7, the method comprising forming at least one layer of the organic films by a coating method.
Citation Information
Patent Citations
Quantum point light emitting element with multiple quantum point layer
JP2010199067A
Crosslinkable Host Materials
JP2017532323A
Polymer compound, composition, liquid composition, thin film, electroluminescent element material and electroluminescent element
JP2018104675A
Polymer compound, material for organic electroluminescence element using same, and organic electroluminescence element
WO2014185079A1